Os significados composicionais e a formação de subjetividades na primeira página de jornais mineiros: um estudo de caso à luz da gramática do design visual - Flaviane Faria Carvalho (2007)
Integrating studies on multimodal texts and print media have become an issue of special concern in the Brazilian academic scenario. Following such a trend, this dissertation aims at furthering such studies by analyzing first-page layouts found on several editions published throughout February 2007 on the most widespread newspapers of Minas Gerais State (Brazil), namely Estado de Minas, Diário da Tarde, Aqui, Hoje em Dia, O Tempo, and Super Notícia. The main objectives of this study are to verify the tendencies of these newspapers in terms of representation of social meanings and development of subjectivities ineach first-page layout, as well as to examine whether format can be regarded as a parameter for the representation of such meanings. The theoretical background for this research comprises social semiotics and multimodality theory. The methodology is built upon the application of systems network involving compositional meanings. The results point out that, on the one hand, the representational resources displayed on Diário da Tarde (a broadsheetlike newspaper) and on Aqui and Super Notícia (tabloid-like newspapers) seem neither to spur readers reflection nor to foster their social, political and cultural development of theirsubjectivities. The reason for such is the fact that these newspapers inure the readers to focus on information related to leisure, rest, entertainment, distraction, consumption or violence, by highlighting the visual component and eventually promoting a smattering of informationunderstanding. On the other hand, the representational elements displayed on the broadsheetlike newspapers Estado de Minas, Hoje em Dia, and O Tempo seem to loosely bring forth a semiotic structure oriented to social, cultural and political development of the readerssubjectivity. This seems to be the result of both their larger provision of textual information on several sections of these newspapers and their organized and systematic display of the leads on the page, which in turn contributes for a better understanding of facts surrounding the readers world. Nevertheless, the newspapers O Tempo and Diário da Tarde (broadsheet-like newspapers) are found to hold features belonging to popular newspapers: the former seems to spur readers consumption and violence more loosely; whereas the later seems to inure the readers to consumption, violence, leisure and entertainment more strikingly. Finally, all the newspapers scrutinized in this study are found to convey soccer news on highly emotional and idealized grounds, which boosts the status of this sport as a value culturally built by the Brazilian society.